Web-Based Administration Applications For Motorcycle Dealers Using FAST Framework - Sinaga, Tantri Hidayati; Hardiansyah, Hary; Dewi, Arie Rafika (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
Administrative management is very important in business, including the motorcycle sales business. The existence of an integrated system to handle administrative activities is absolutely necessary to increase work efficiency and tidy up the storage of related documents. In this research, the development of an administration system for motorcycle dealers will be carried out using the FAST Framework. FAST Framework was chosen because of its ability to support rapid application development. In this study, FAST Framework will be carried out in five stages, namely scope definition, problem analysis, requirements analysis, logical design and physical design for the development of motorcycle dealer administration applications, so that applications will be produced that suit user needs. The results of this study will be used to collect data on license plates, collect data on vehicle registration, collect data on motorcycle down payment, and collect data on motorcycle sales. From the results of this study, an application has been produced that will facilitate business administration and service customer data needs. The resulting application has been tested and can run well to handle the necessary business administration needs. Through the application produced by this research, consumers also no longer need to come directly to the dealer to check the status of motor vehicle registration because it can be done online.